HNGF6A ameliorates oxidative stress-mediated mitochondrial dysfunction in degenerative meniscus - Ruonan Liu; Xue Du; Yufeng Chen; Zijing Zhu; Zongrui Jiang; Chengyun Zhang; Dong Jiang; Zhiqi Zhang (Bone & Joint Research)
Aims: Meniscus injury can lead to knee synovitis and cartilage deterioration, ultimately resulting in osteoarthritis (OA). Mitochondrial dysfunction has been identified as an induction factor in OA development, owing to an imbalance between the production of reactive oxygen species (ROS) and the antioxidant capacity of cells. However, the contribution of mitochondrial function in the meniscus to OA remains unclear. The purpose of this work was to elucidate the impact of HNGF6A, a mitochondrial-derived protective peptide, on meniscus senescence and degeneration to clarify the underlying mechanisms of ROS-induced OA pathogenesis. Methods: Primary human meniscus cells were subjected to oxidative stress using tert-butyl hydrogen peroxide (TBHP). Mitochondrial function and ROS levels were evaluated using transmission electron microscopy (TEM), cytometry, and immunofluorescence. C57BL/6 mice subjected to destabilization of the medial meniscus (DMM) were either administered or not administered HNGF6A, and gait analysis was performed at eight weeks after surgery. Knee joints were collected for graft micro-CT and histological staining. Results: Mitochondrial function was found to be impaired in the degraded menisci in OA. Pretreatment with HNGF6A significantly restored the matrix degradation and cell apoptosis induced by TBHP, and maintained mitochondrial redox homeostasis, which corresponded with the activation of autophagy and FUN14 domain containing 1 (FUNDC1) upon HNGF6A treatment. The animal studies also revealed that HNGF6A alleviates meniscus degeneration and osteophyte volume, and ameliorates the OA phenotype in vivo. Conclusion: HNGF6A was found to protect meniscus cells by restoring FUNDC1-mediated mitochondrial redox homeostasis and autophagy. Thus, HNGF6A may have therapeutic applications in the prevention and treatment of meniscal degeneration and OA progression. Cite this article: Bone Joint Res 2025;14(4):315–327.